2020
DOI: 10.1038/s41591-020-0754-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt substitution on community-wide blood pressure and hypertension incidence

Abstract: reduction in salt intake has been identified as one of the most cost-effective measures for improving health outcomes 1-3. Different studies have reported the benefit of salt-reduction interventions in decreasing blood pressure and cardiovascular events 4-6. Results from a meta-analysis show that modest reductions in salt intake are followed by a decrease in blood pressure levels among both hypertensive and normotensive subjects 7. Nevertheless, the evidence of the effectiveness of population-level, behavior c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
146
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(160 citation statements)
references
References 47 publications
4
146
1
9
Order By: Relevance
“…Although to contain and reverse the recently observed slowdown and stagnation of CVD burden must be the highest priority for the entire Region, the challenge is even greater for the LMIC because they do not have enough resources neither the health system prepared to resist this enormous burden. This challenge requires a more innovative, socially inclusive, and strategic effort to implement evidence‐based low‐cost interventions with potential to safe millions of deaths, such as salt reduction through the replacement of regular salt with potassium‐enriched substitutes which can reduce blood pressure and hypertension incidence, 38 elimination of artificial trans‐fat, and improvement of hypertension management in primary care through simple standardized treatment protocols, a core set of medications, team‐based care and closely monitor patient progress and system performance 39 . Along with theses key interventions, this Region and particularly its most vulnerable economies can benefit significantly with more aggressive measures to reduce tobacco use and to overturn the obesity epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Although to contain and reverse the recently observed slowdown and stagnation of CVD burden must be the highest priority for the entire Region, the challenge is even greater for the LMIC because they do not have enough resources neither the health system prepared to resist this enormous burden. This challenge requires a more innovative, socially inclusive, and strategic effort to implement evidence‐based low‐cost interventions with potential to safe millions of deaths, such as salt reduction through the replacement of regular salt with potassium‐enriched substitutes which can reduce blood pressure and hypertension incidence, 38 elimination of artificial trans‐fat, and improvement of hypertension management in primary care through simple standardized treatment protocols, a core set of medications, team‐based care and closely monitor patient progress and system performance 39 . Along with theses key interventions, this Region and particularly its most vulnerable economies can benefit significantly with more aggressive measures to reduce tobacco use and to overturn the obesity epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…15 In a recently published randomized intervention in Peru, use of a 25% potassium salt substitute corresponded with reductions in SBP of 1.29 mm Hg (P = .04) in a population sample and by 1.92 mm Hg (P = .006) in a subgroup of participants with hypertension. 25 Decreasing incidence of CVD (13.1 per 1000 persons vs 20.5 per 1000 persons) have also been reported in a randomized intervention of adult males receiving a 50% potassium salt substitution. 24 However, the authors noted only modest reductions in sodium intake within this experimental group.…”
Section: Electrolytes and Cardiovascular Disease Riskmentioning
confidence: 90%
“…Each village crossed over from the control condition (no salt substitution) to the intervention (community-wide salt substitution) sequentially, in an order determined by randomization, and remained in the intervention condition until the end of the study, so that salt substitution was implemented in all villages (known as a 'stepped-wedge' design). The results showed that salt substitution caused a reduction in BP by 1.23 (0.38-2.07) mmHg/0.72 (0.10-1.34) mmHg (systolic/diastolic) in all participants, and in those with normal BP, hypertension incidence was halved 4 . These findings provide further support for the use of salt substitutes as a population-level strategy to prevent hypertension.…”
mentioning
confidence: 95%
“…A recent meta-analysis of 13 randomized trials showed that replacing the usual salt with low-sodium, high-potassium salt substitutes reduced BP to a degree of clinical and public-health importance 3 . A study by Bernabe-Ortiz et al, published in this issue of Nature Medicine, is the latest addition to efforts in extending the use of salt substitutes from clinical-trial settings to the population level 4 . The authors used a stepped-wedge cluster randomized trial design in six villages in northern Peru to replace the usual salt with a salt substitute and found that salt substitution will most likely have health benefits.…”
mentioning
confidence: 99%